(untitled) (International Journal of Engineering and Computer Science, 2018)
The purpose of this paper is to study components of a theoretical Enterprise Data Warehouse within the context of a higher education environment. The reason for such an implementation would give users at all levels of the university an integrated, secure and consistent data source from which they could report on and set their business needs more efficiently than possible without one